Combination of Pseudomonas aeruginosa and Rhamnolipid for Bioremediation of Soil Contaminated with Waste Lubricant Oil - Lopes, P. R.M. [UNESP]; Montagnolli, R. N.; Dilarri, G.; Mendes, C. R. [UNESP]; Cruz, J. M. [UNESP]; Bergamini-Lopes, M. P. [UNESP]; Moreira, B. R.A.; Contiero, J. [UNESP]; Bidoia, E. D. [UNESP] (Pleiades Publishing, 2024)
Abstract: Lubricant oils are largely responsible for environmental contamination and surfactants can hopefully improve the bioremediation process in soils contaminated with this kind of waste. However, to date only a few studies have elucidated how different surfactants affect the bioremediation process in oil-contaminated soils using the bioaugmentation technique. Thus, this study aimed to compare the effects of surfactants on the bioremediation process of waste lubricant oil in soil in association or not with bioaugmentation. Three biostimulating agents were tested: a chemical detergent, a synthetic surfactant, and a biosurfactant (rhamnolipid). The bioaugmentation process with Pseudomonas aeruginosa showed a faster biodegradation activity with total biodegradation on 181 day after application. The biosurfactant increased the number of microbial and fungal colonies leading to high biodegradation levels and a quicker treatment with or without the bioaugmentation. Bioaugmentation associated with biosurfactant reached 30.43 mg of CO2 of production on 181 day (90% of total biodegradation of waste lubricant oil) and reduced soil toxicity to 30%. Therefore, results showed that the association of biosurfactant and bioaugmentation with P. aeruginosa represents an ecologically viable strategy for bioremediation of soils contaminated with waste lubricant oil.
Keywords: bioaugmentation; biodegradation; ecotoxicity; petroleum; soil microorganisms; surfactant